A Psycholinguistic Approach to Inmate Argot in Romanian Prisons - Nădrag, Lavinia; Stroescu, Manuela (Instytut Językoznawstwa Wydział Neofilologii, UAM, 2010)
The lexis and structure of prison argot reflect the personalities of inmates who employ them, as well as the conflicts and tensions inherent in prison settings. It is shown in this article that the distinctiveness of prison argot is largely a product of the character of penal context. Its extent of use varies with the extent of penal discipline. Appreciation of this complex relationship might facilitate improved communication between prisoners and custodial authorities. In addition, knowledge of prison argot meanings has a potential to improve the management of prison-based programs and thus appears helpful in the complex process of prisoners' rehabilitation and social reintegration.

Lexicul şi structura argoului din închisori reflectă atât personalitatea condamnaţilor care le utilizează, cât şi conflictele şi tensiunile inerente în închisori. În acest articol, se arată că particularităţile argoului din închisori sunt, în mare măsură, un produs al caracterului contextului penal. Utilizarea sa variază în funcţie de disciplina penală. Cunoaşterea acestei relaţii complexe ar putea facilita comunicarea dintre persoanele private de libertate şi autorităţile care le au în custodie. În plus, cunoaşterea sensurilor argoului penitenciar are potenţialul de a îmbunătăţi managementul programelor din penitenciar şi, astfel, poate fi de mare ajutor în procesul complex de reabilitare şi reintegrare socială a condamnaţilor.
Psycholingwistyczne podejście do żargonu więźniów w rumuńskich zakładach penitencjarnych
Un studiu asupra argoului din penitenciarele româneşti
Keywords: study; argot; slang; inmate; prison